Planning strategic management for theme park tourism: Evidence from Indonesia - Widjaja, Herry Rachmat; Junaid, Ilham; Ilham, Muhammad Dzakwan Mufadhdhal (Journal of Applied Sciences in Travel and Hospitality, 2025)
Limited studies discuss parks and tourism. The factors that influence the sustainability of a park have yet to be the concern of academics. Planning based on strategic management is a critical step in managing a park that has experienced a decline in management quality. This study aims to 1) identify the actual condition of park as a tourist attraction; 2) describe the factors supporting and inhibiting the management of park as a tourist attraction from the perspective of residents; 3) evaluate Maccini Park as a tourist attraction for visitors: 4) propose the planning and management of a park as a tourist attraction. This study employed a mixed-methods approach through interviews, observations, and surveys in January 2023. The research utilised primary data from the public and visitors to the park and secondary data through internet data review. The study results show that Maccini Sombala Park became the public’s and visitors’ primary choice for tourism when it opened in 2003. Covid-19 has had an impact on the unsustainable management of the park. Free entry of visitors and the public and low public awareness in maintaining tourist parks inhibit the park’s management. As a result, there are damaged and stolen facilities and irresponsible visits. The park can support urban tourism development due to factors such as strategic location, tourism support facilities, government efforts in managing the park and positive information on the internet media. This research advances the knowledge of strategic planning in park management from the perspective of theme park tourism. Practically, implementing a planning mechanism may overcome the issue of unsustainable management.